Mango production in major areas in Davao region efficiency, markets and margins - Castillo, Alex Kavin B.
The Philippine Carabao mango had established its reputation locally and internationally as a superior breed and quality among other varieties in the world but its supply pales in comparison with the local and international demand. Moreover, Philippine mango industry is facing three major issues; efficiency in terms of profit generation, complex market structure brought by different actors in the supply chain and the likelihood of disproportionate benefit sharing in terms of profit margins by these actors. Hence, this study was conducted to identify issues and opportunities in the mango industry in three major areas in Davao region- Davao City, Digos City and IGACOS. Specifically, it aimed to measure the efficiency of mango farmers in terms of profit generation and identify the factors affecting efficiency; identify the roles of different actors in the mango industry; and assess the profitability of the actors and identify the factors affecting profitability. Multiple approaches were used to answer the objectives including Data Envelopment Analysis-Tobit Analysis, Value Chain Analysis, and Net Margin Analysis. Results suggest that the inter-relatedness of farmers, financiers, and middlemen has primary effect on the distribution of benefits among the actors in the mango supply chain. Profitablity in mango farming favours those farmers having more trees with mature age, relatively older farmers with more experience and those that are under financing. Medium farmers in Digos City predominantly have these specific attributes. There are price premia for producing quality mangoes with export and Manila markets being viable marketing options. Wholesaling activities are favoured in Digos City due to minimal marketing costs while retailing activities are best in Davao City due to larger captured market specifically in Bankerohan public market.